Pemanfaatan Media Wordwall.net Sebagai Media Evaluasi dalam Pembelajaran Bahasa Indonesia - Putti Larasati; Ida Bagus Putrayasa; I Nengah Martha (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The use of Wordwall.net media as an evaluation medium in learning Indonesian is considered very suitable. Because it has many templates that can be changed easily by the teacher or teacher and games that have been designed by the teacher. This study used descriptive qualitative method. Researcher used the Wordwall.net media which was used in Indonesian language learning of class VII students of SMP Negeri 2 Seririt. Primary data is the result of observations of class VII students of SMP Negeri 2 Seririt. Secondary data is scientific writing or previous research regarding the use of educational games Wordwall.net. Wordwall.net can be used anytime and anywhere, not only as a learning medium, but also as a learning evaluation medium. Apart from being free and also without downloading an application, Wordwall.net has a wide variety of games and is very suitable for learning Indonesian. The use of learning media Wordwall.net as an evaluation medium in supporting learning can make it easier for teachers to analyze and obtain learning evaluation results, especially learning Indonesian.